The Development of a Digital Electronics Trainer for Teaching Fundamentals of Electronics Engineering - Suryani, Titin; Anis, Samsudin; Arief, Ulfah Mediaty (Universitas Negeri Semarang, 2024)
The teaching of Fundamentals of Electronics Engineering often faces challenges in bridging theoretical knowledge with practical application. A lack of interactive and contextual learning media hinders students’ comprehension of foundational concepts and diminishes their motivation to learn. This study addresses these challenges by developing a digital electronics trainer as an instructional tool to support the learning process. The trainer is designed and implemented to help students explore digital electronics concepts—specifically logic gates—through relevant problem-solving activities. The aim is to enhance students’ conceptual understanding and engagement. This research employs a Research and Development (R&D) approach, utilizing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results demonstrate the significant effectiveness of the digital electronics trainer in improving students’ cognitive abilities. An N-Gain score of 0.71 indicates a high level of cognitive improvement in the experimental group using the trainer, compared to the control group that relied on textbook-based learning.